Root bacterial endophytes as potential biological control agents against fungal rice pathogens. (9th May 2019) - Etesami, Hassan; Alikhani, Hossein Ali; Mirseyed Hosseini, Hossein
Abstract: The present work was carried out to investigate the potential of 100 rice endophytic bacteria for the biocontrol of five fungal rice pathogens in a controlled environment. As well as, isolates with antagonistic activity were also characterized in terms of production of some plant growth promoting (PGP) traits. Twenty-three isolates repressed the mycelial growth of some fungal rice pathogens (70–96% inhibition). The results illustrated that production ability of PGP traits was different among biocontrol isolates. Higher % of the isolates was positive for generation of ACC deaminase, IAA, and activity of cellulase and pectinase. The effective isolate was identified as Bacillus cereus . This strain also colonized root of rice seedlings and increased root fresh weight (31.4%) and shoot dry weight (28.2%) in vitro . These results showed that endorhiza of rice harbors effective antagonistic bacteria with multiple PGP traits which can be used as a potent biocontrol or biopromoting agent in rice plant.